Kinematic profile of elite high jumpers - what distinguishes good from great high jumpers? - Petrovic, M.; Gisladottir, T. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: It has been shown that the success in high jump very often relies on the ability of a jumper to manipulate biomechanical factors that are closely related with optimization of the. Effectiveness in high jumping largely depends on the take-off (TO) action, contact time with the ground, ankle, and knee angles at touch-down (TD) and TO, height of the center of mass (CoM) at TO. We hypothesized that the highest successful attempt will be correlated with kinematic parameters related to peak CoM and peak pelvis position.